Analysis of serum lactate levels to predict in hospital mortality in critically ill children admitted to pediatric intensive care unit - Srigiri, Trilok Rao; Manyam, Partha Saradhi; Mahesh, Uma; Belavadi, Gangadhar (International Journal of Contemporary Pediatrics, 2019)
Background: The predictive significance of lactate measurement at admission for mortality in critically ill children remains uncertain. Authors objectives was to study evaluated the predictive value of blood lactate levels at admission and determined the cut-off values for predicting in-hospital mortality in the critically ill pediatric population. Methods: A prospective observational study was done in 100 critically ill admissions to the pediatric intensive care unit (PICU), requiring hemodynamic/respiratory support. The chi-square test for categorical variables performs the comparison. Results: Out of 100 patients, 22 (22%) expired. Mortality is highest in 10-16 age (7%). In the non-survivor group, the majority of patients were diagnosed as pneumonia (7.5%). Median lactate levels in non-survivors are 4.5 at admission when compared to 2.0 in survivors (p<0.001). The mortality rates left rate in the high lactate group (73%) is more when compared to intermediate (20%) and low-level groups (7%). Blood lactate was 75% sensitive and 90% specific at the optimal cut-off value of 33.7 mg/dl. The positive likelihood ratio of predicting death is more with a high lactate level (7.5) when compared to intermediate (0.8) and low levels (0.08). Sensitivity and Specificity with elevated lactate levels is the mortality 24 hrs (89%, 92%) than at admission (75%, 90%). The AUROC values with the admission lactate level are 0.86, and after 24 hrs are 0.95. Conclusions: Blood lactate levels at admission predict mortality in critically ill children requiring hemodynamic/respiratory support.